Strategy to control and eradicate dengue hemorrhagic fever vectors in Bali - I Made Dwi Mertha Adnyana; Asik Surya (International Journal of Public Health Science (IJPHS), 2023)
Dengue hemorrhagic fever cases in Bali have increased in the past decade. Control and eradication efforts must be optimized. In order to create dengue-free zones, accurate information and a comprehensive strategy for accelerating dengue vector management are required. This paper is based on empirical, field, and epidemiological studies and program evaluations guided by the health belief model approach. In this regard, Bali's lesson on dengue cases fluctuated from 2018 to 2020. The incidence and death rates are increasing, especially during the COVID-19. Many factors affect the disease agent, the host, and the environment. The SIGAP strategy is a policy brief that is studied and implemented to accelerate dengue vector control in Bali, which includes: awareness of the importance of 4M-Plus (draining, closing, reusing used goods, and monitoring) and mosquito nest control; integration of dengue information services; using natural insecticides and larvicides; observing and reporting the presence of vectors to the larva monitoring officer; and regular monitoring weekly. Implementing the SIGAP strategy can reduce dengue vectors and speed up the process of getting rid of dengue disease in Bali.